2016
DOI: 10.4172/2375-446x.1000150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extraction Methods on the Yield and Physiochemical Properties of Polysaccharides Extracted from Seaweed Available in Sri Lanka

Abstract: Agar, carrageenan and alginate are high valued seaweed polysaccharides, which are used as gelation and thickening agents in different food, pharmaceutical and biotechnological industries. The annual global production of the polysaccharides has recently reached 100,000 tons with a gross market value just above US$ 1.1 billion. In Sri Lanka although several seaweed species are available, there is no systematic study on comparison of method of extraction, yield and physicochemical properties of polysaccharides fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Regarding the mineral composition of EAP extract, the results presented in Table 2 show that sodium was the most abundant mineral (223.2 mg/100 g), followed by calcium (197.85 mg/100 g), and then potassium (108.5 mg/100 g). As reported by Jayasinghe et al [26], the commercial agar contains a similar amount of Mg and K, whereas EAP present high levels of Na and Ca. The measurement of Aw shows that the EPA present an Aw of 0.37 ± 0.006, which is situated according to the map of stability in an area where the oxidation of lipids is low, non-enzymatic browning (Maillard reaction) is slow, and the enzyme activities are required to prevent the development of microorganisms.…”
Section: Eap Content and Chemical Compositionsupporting
confidence: 63%
See 2 more Smart Citations
“…Regarding the mineral composition of EAP extract, the results presented in Table 2 show that sodium was the most abundant mineral (223.2 mg/100 g), followed by calcium (197.85 mg/100 g), and then potassium (108.5 mg/100 g). As reported by Jayasinghe et al [26], the commercial agar contains a similar amount of Mg and K, whereas EAP present high levels of Na and Ca. The measurement of Aw shows that the EPA present an Aw of 0.37 ± 0.006, which is situated according to the map of stability in an area where the oxidation of lipids is low, non-enzymatic browning (Maillard reaction) is slow, and the enzyme activities are required to prevent the development of microorganisms.…”
Section: Eap Content and Chemical Compositionsupporting
confidence: 63%
“…This value was higher than that obtained for butylated-hydroxyanisole (BHA) (IC 50 = 0.4 mg/mL) used as the positive control. Despite the lower antioxidant activity compared with that of BHA, the obtained results indicated that EAP present an interesting natural antioxidant extract [26].…”
Section: Determination Of Total Antioxidant Capacity (Tac)mentioning
confidence: 78%
See 1 more Smart Citation
“…This chelation process is highly associated with mannitol, a natural chelating agent. This chelating agent could provide micronutrients within the soil, revitalise the soil structure, and increase water reservoir capacity suitable for plants and crops [30].…”
Section: Discussionmentioning
confidence: 99%